Clinical appearance of oral mucous in children with Î²-major thalassemia - Lova, Areta Tera; Chemiawan, Eka; Dewi, Tenny Setiani (Padjadjaran Journal of Dentistry, 2011)
Beta major thalassemia is characterized by severe hereditary hemolytic anemia. The oral mucous of children with beta major thalassemia becomes yellow grayish due to the combination of pallor, icterus/yellowish and grayish pigmentation. The purpose of this research was to obtain a clinical data of oral mucous color of beta major thalassemia childrens patients at the Thalassemia Polyclinic of Pediatric Department in Dr. Hasan Sadikin General Hospital Bandung in December 2009 until January 2010. This research was the description method with survey technique. The sampling technique was consecutive sampling. The sample was collected in one month and resulting 129 sample. The data obtained by clinical evaluation of each part of oral mucous. Research result showed that the clinical color of oral mucous of beta major thalassemia children patients becomes pallor, yellowish, yellow, yellow grayish, yellow blackish differently of each part of oral mucous. Pallor mostly at tongue, yellowish at buccal mucous, yellow at soft palate, yellow grayish at sublingual, hard palate, gingival, and yellow blackish at hard palate. The conclusion of this research was that the color of the oral mucous beta major thalassemia children patients was changed and was different with the color of oral mucous in normal children.